Convergence or Divergence in Economic Growth of Commonwealth of Independent States (CIS) - Shah, Imtiyaz Ahmad; Haq, Imtiyaz ul (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
In this study, the issue of economic growth and Convergence in the 12 countries of the CIS region has been investigated thoroughly for 27 years, from 1991-2017. The paper examines the absolute, sigma and conditional Convergence of the CIS region. Conditional Convergence is examined through the augmented Solow and extended Solow models. During the study period, the empirical results confirm no significant negative correlation between the initial ratio of the countries per capita GDP and the average yearly growth rate. Thus, indicating the absence of absolute β convergence across the CIS economies during 1991–2017. The results of the sigma convergence are consistent with the results derived from the absolute convergence model. Referring to the augmented Solow model estimations, we found the rate of conditional β-convergence (coefficient of initial GDP per capita) of value 0.028 among members of the CIS region after controlling GDP per capita, physical and human capital and population growth have important contributions to make in the growth and Convergence of countries. In Solow extended growth regression, the initial GDP per capita coefficient is 0.33. Therefore, besides the initial level of per capita income, physical and human capital and population growth, other factors have important contributions to make to the growth and Convergence of countries of CIS.